PERENCANAAN INSTALASI PENGOLAHAN AIR BERSIH DENGAN SARINGAN PASIR LAMBAT “UP FLOW” DI KAMPUS UNIVERSITAS PASIR PENGARAIAN KABUPATEN ROKAN HULUPROPINSI RIAU - Purwo Subekti; Anton Ariyanto; Frans Yadi Simamora (Jurnal APTEK, 2012)
Until this this day the proper water consumption supply problem at the Pasir Pengaraian University campus still continues. The need for clean water is one of the contributing factors that can not be ignored for the smoothness activity of the campus environment. By not proper the water, directly impacting to activities support on campus will be distrubed. For the treatment of raw water to water consumption required inexpensive technology for water treatment, the installation of Slow Sand Filter (SSF) Up Flow is an alternative that can be used.From the research results can be determined a maximum daily requirement per day is 17.03 m³ / h, discharge of raw water in the pool is 76.65 m³ / h, the surface area of pool water sources is 191, 63 m², SSF tub surface area is 63.88 m² and budget plan is needed to create a pool of water sources and the SSF is Rp. 87.926.300